Cultural codes provide novel strategies for mental training - Ge, Y.; Zhang, L. (Advances in mental skills training, 2021)
Culturally competent mental training practices represent a holistic view of athletes. Traditional sport psychology tends to focus on the performance aspects of athletes, while ignoring other aspects of their lives. The performancecentered narratives in sport psychology, which emphasized dedication, masculinity, toughness, and competition, jeopardizes athletes` well-being and long-term development. Wylleman, Alfermann, and Lavallee (2004) suggested a holistic, life-span developmental perspective to understand athletes` transitions in their athletic careers as well as in other domains of the their lives, including the changes they encounter at a psychological level (from adolescence into young adulthood), a psychosocial level (development of temporary or stable relationships with a partner), and at the academic or vocational level (transiting into higher education or into a professional occupation). Henriksen, Stambulova, and Roessler (2010) advocated for a holistic ecological approach to investigate the environment in which athletes develop, analyzing family, peers, schools, cultures, organization, sport system, team history, and other contextual factors that contribute to athletes` successes in career transitions. Miller and Kerr (2002) stated, "Performance excellence is attained only through optimal personal development". Through a comprehensive understanding of athletes` lives and the sociocultural contexts, researchers and practitioners move from the mechanical view of mental process to focusing on the overall development of athletes.